(untitled) (Heritage, 2024)
As a large town in the southeastern part of the Kingdom of SHS, Kumanovo was suitable tor the work of financial institutions, especially since no bank operated there until 1921 when at the end of the year Kumanovo Commercial and Industrial Bank was founded. Over time, two banks from Vranje opened branches in this city, and from 1928, the Kumanovo Export and Traffic Bank also operated. The founders of this bank were persons who were already shareholders of the Kumanovo Commercial and Industrial Bank, among whom the most famous was Ilija Vukotić, the national representative. The political involvement of Vukotić and Ćira Manević, the president of the Board of Directors of the Kumanovo Commercial and Industrial Bank on opposite sides, hints at the political background of the establishment of this financial institution. The bank operated successfully until the outbreak of the banking crisis in the Kingdom of Yugoslavioa in 1931, and its position was further compicated by the adoption of the Law on the Protection og Farmers in 1932. The bank paid its obligations until 1936, when it was forced to put itself under protection. In the following years, this institution was an example of the legal application of the moratorium and reduction of inst obligations to investors. Through its operations, the bank carried out a silent liquidation, and its management tool upon itself the burden of unfavorable conditions for the work of banks in the Kingdom of Yugoslavia during the thirtes of thetwntieth century.